Osmotic demyelination syndrome: revisiting the diagnostic criteria through two fatal cases - Biancamaria Treves; Francesca Consalvo; Giuseppe Delogu; Donato Morena; Martina Padovano; Alessandro Santurro; Matteo Scopetti; Vittorio Fineschi (BMC Neurology)
Abstract Background Osmotic Demyelination Syndrome (ODS) encompasses Central Pontine Myelinolysis and Extrapontine Myelinolysis, both of which are serious neurological conditions linked to the overly rapid correction of hyponatremia. Despite growing evidence, the exact etiology of ODS remains incompletely understood. The present paper describes two case studies, aiming to provide a comprehensive overview of the pathological findings and clinical outcomes associated with ODS. Case presentation Case #1. A 74-year-old woman was admitted to the emergency department following a head trauma caused by a loss of consciousness. Initial laboratory tests revealed severe hyponatremia (sodium level of 101 mmol/L) and hypokalemia (potassium level of 2.9 mmol/L). The patient underwent corrective therapy with saline and potassium chloride. Despite the correction of electrolyte imbalances, the patient developed a hyperintense lesion in the median portion of the pons on T2-fluid-attenuated inversion recovery (FLAIR) MRI sequence 14 days post-treatment, consistent with ODS. The patient’s condition deteriorated, leading to irreversible coma and status epilepticus, culminating in death 32 days after admission. Case #2. An 81-year-old woman with a medical history of hypothyroidism, hypertension, major depression, and stage 3 chronic kidney disease presented with mild gait disturbances. Subsequent testing revealed severe hyponatremia (sodium level of 100 mmol/L). Following an initial clinical improvement due to sodium correction, the patient’s condition worsened, with symptoms progressing to confusion, lethargy, and eventually, ODS. Dermatological manifestations, including blistering lesions and facial edema, appeared as the condition advanced. The patient succumbed to irreversible coma 47 days after admission. Conclusion ODS traditionally carried a poor prognosis, with high mortality rates and diagnoses often made postmortem. However, recent advances in understanding the pathophysiology, along with improvements in diagnostic techniques such as MRI and intensive care treatments, have led to earlier identification, treatment, and recognition of milder forms of the syndrome. Despite these advancements, ODS remains a critical condition with significant risks, particularly following the rapid correction of severe hyponatremia.